Tartessos and the Phoenicians in Iberia - Celestino Pérez, Sebastián 1957-; López-Ruiz, Carolina (Oxford University Press, 2016)
This is the first book in English about the earliest historical civilization in the western Mediterranean, known as "Tartessos". It combines the expertise of its two authors in archaeology, philology, and cultural history to present a comprehensive, coherent, theoretically up-to-date, and informative overview of the discovery, sources, and debates surrounding this puzzling culture of ancient Iberia and its complex hybrid identity vis-à-vis the western Phoenicians
Keywords: Phöniker; Tartessos